Effects of Microplastic Fibers on Soil Aggregation and Enzyme Activities Are Organic Matter Dependent - Liang, Yun; Lehmann, Anika; Yang, Gaowen; Leifheit, Eva F.; Rillig, Matthias C. (Frontiers in Environmental Science, 2021)
Microplastic as an anthropogenic pollutant accumulates in terrestrial ecosystems over time, threatening soil quality and health, for example by decreasing aggregate stability. Organic matter addition is an efficient approach to promote aggregate stability, yet little is known about whether microplastic can reduce the beneficial effect of organic matter on aggregate stability. We investigated the impacts of microplastic fibers in the presence or absence of different organic materials by carrying out a soil incubation experiment. This experiment was set up as a fully factorial design containing all combinations of microplastic fibers (no microplastic fiber addition, two different types of polyester fibers, and polyacrylic) and organic matter (no organic matter addition, Medicago lupulina leaves, Plantago lanceolata leaves, wheat straw, and hemp stems). We evaluated the percentage of water-stable aggregates (WSA) and activities of four soil enzymes (β-glucosidase, β-D-celluliosidase, N-acetyl-b-glucosaminidase, phosphatase). Organic matter addition increased WSA and enzyme activities, as expected. In particular, Plantago or wheat straw addition increased WSA and enzyme activities by 224.77% or 281.65 % and 298.51% or 55.45%, respectively. Microplastic fibers had no effect on WSA and enzyme activities in the soil without organic matter addition, but decreased WSA and enzyme activities by 26.20% or 37.57 % and 23.85% or 26.11%, respectively, in the presence of Plantago or wheat straw. Our study shows that the effects of microplastic fibers on soil aggregation and enzyme activities are organic matter dependent. A possible reason is that Plantago and wheat straw addition stimulated soil aggregation to a greater degree, resulting in more newly formed aggregates containing microplastic, the incorporated microplastic fibers led to less stable aggregates, and decrease in enzyme activities. This highlights an important aspect of the context dependency of microplastic effects in soil and on soil health. Our results also suggest risks for soil stability associated with organic matter additions, such as is common in agroecosystems, when microplastics are present.